2018
DOI: 10.1002/gcc.22675
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor I X is a recurrent target for HPV16 insertions in anal carcinomas

Abstract: Anal carcinomas (AC) are associated with human papillomavirus (HPV) DNA sequences, but little is known about the physical state of the viral genome in carcinoma cells. To define the integration status and gene(s) targeted by viral insertions in AC, tumor DNAs extracted from 35 tumor specimen samples in patients with HPV16‐associated invasive carcinoma were analyzed using the detection of integrated papillomavirus sequences‐PCR approach. The genomic status at integration sites was assessed using comparative gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
3
6
0
1
Order By: Relevance
“…These recurrent insertions were not detected in HPV-positive ASCC. In contrast, integration into the NFIX gene was observed in four cases, confirming the results from the recent study by Jeannot et al [15], along with three other integration events adjacent to the NFIX gene but nonintragenic, of unknown significance. NFIX belongs to the NFI gene family, consisting of four transcription factors (NFIA, NFIB, NFIC, and NFIX), involved in the regulation of cell proliferation and differentiation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These recurrent insertions were not detected in HPV-positive ASCC. In contrast, integration into the NFIX gene was observed in four cases, confirming the results from the recent study by Jeannot et al [15], along with three other integration events adjacent to the NFIX gene but nonintragenic, of unknown significance. NFIX belongs to the NFI gene family, consisting of four transcription factors (NFIA, NFIB, NFIC, and NFIX), involved in the regulation of cell proliferation and differentiation.…”
Section: Discussionsupporting
confidence: 89%
“…The distribution of the various HPV integration signatures differed between ASCC and cervical cancers and was associated with viral load and PIK3CA mutation [18]. The small number of events in this single-center study may have limited the statistical power to determine whether HPV status and integration signatures have a prognostic or predictive impact in HPV-positive ASCC, but was nevertheless sufficient to confirm recurrent targeting of NFIX by HPV insertion in ASCC, a potential favorable prognostic factor [15]. Further studies on larger, multicenter cohorts of anal and other HPV-associated tumors are warranted.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The HBV regions included in this integrant are shown in Figure 2 D. The insertion point of human chromosome 17 is the coiled-coil domain-containing 57 (CCDC57) coding region. It has been reported that CCDC57 is one of the genes targeted by the integration of human papillomavirus 16 (HPV 16) [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…FLOT1 also induces EMT and alters cell cycle by modulating Erk/Akt signaling axis 31 . Besides, the prognostic value of IL20RB was actively discussed in multiple tumors including glaucoma, anal cancer and lung adenocarcinoma [32][33][34] . Moreover, MAPKAPK3 is a member of stress-responsive kinase that induces autophagy in terms of stress (in ammation, infection and starvation)and thus determining cell fate 35,36 .…”
Section: Discussionmentioning
confidence: 99%